Satisfaction with life and its socio-personal correlates in adolescents from public middle schools in Sonora, Mexico - Lagarda Lagarda, Angel Emigdio (2022)
The objective of the study was to measure the relationship of personal variables and context with satisfaction with the life and personal well-being of school adolescents in northwestern Mexico. The design is non-experimental ex post facto of transversal type. Two samples of high-low satisfaction with life and personal well-being were compared. Discriminant analyzes and logistic regressions were performed. In the analyzes, the Local Well-being Index, the Family Self-concept and the Social Self-concept result as predictive variables of Personal Well-being, adding to the Neighborhood Attachment in the prediction of Satisfaction with Life. It is concluded that it is important to develop ecological models that include multilevel variables to explain and predict the subjective well-being.